Granular Materials - Sakellariou, Michael (IntechOpen, 2017)
This volume presents basic notions and fundamental properties of granular materials covering a wide spectrum of granular material mechanics. The granular materials may behave as fluids or solids or both. The grain size may span from microscopic to macroscopic scale. From the wet sand effect, Reynolds inspired in 1885 the notion of granular universe introducing the term "dilatancy." Bak, Tan, and Wisenfeld (1987, 1988) used the sand pile as a representative model of complex systems. In this collection of chapters, granular dynamics, granular flow from dilute to jammed states, dynamics of granular gas in microgravity, particle jetting induced by impulsive loadings, particle migration phenomena in embankment dams, and the grading entropy-based criteria of granular materials and filters are presented.